Quality of life and physical components linked to sarcopenia: The SarcoPhAge study - Beaudart, C.; Reginster, J.Y.; Petermans, J.; Gillain, S.; Quabron, A.; Locquet, M.; Slomian, J.; Buckinx, F.; Bruyère, O. (Experimental gerontology, 2015)
The SarcoPhAge project is an ongoing longitudinal study following community-dwelling elderly subjects with the objective to assess some health and functional consequences of sarcopenia. The sarcopenia diagnosis algorithm developed by the European Working Group on Sarcopenia in Older People (EWGSOP) and used in the present study needs further validation through cross-sectional and longitudinal studies. The aim of the present study is to assess, using this algorithm, the prevalence of sarcopenia and the clinical components linked to this geriatric syndrome. Participants were community dwelling subjects aged 65years or older. To diagnose sarcopenia, we applied the definition of the EWGSOP. Muscle mass was measured by dual-energy X-ray absorptiometry, muscle strength by a hydraulic dynamometer and physical performance by the SPPB test. Large amounts of socio-demographic, anamnestic and clinical data were collected in all subjects. 534 subjects were recruited for this study (60.5% of women, mean age of 73.5±6.16years), among whom 73 subjects were diagnosed sarcopenic, which represents a global prevalence of 13.7%. Prevalence was 11.8% in men and 14.9% in women. Sarcopenic subjects were older; had a lower Body Mass Index, lower calf, waist, wrist and arm circumferences; presented more cognitive impairments (Mini-Mental State Examination), more comorbidities; were more often malnourished; and consumed more drugs. After adjustment for age, BMI, cognitive status, nutritional status, number of comorbidities and number of drugs, sarcopenic subjects had a worse physical health-related quality of life (SF-36) for the domain of physical functioning, were at higher risk of falls (Timed Up and Go test), were more frail (Fried), presented more often tiredness for the achievement of activities of daily living (Mobility-test), presented less fat mass and obviously less lean mass. Sarcopenic women were also more dependent for housekeeping and handling finances (Lawton scale) than non-sarcopenic ones. Sarcopenia seems to be associated with many harmful clinical components making this geriatric syndrome a real public health burden. Follow-up data of the SarcoPhAge study will be helpful to assess the outcomes of sarcopenia based on the EWGSOP diagnosis algorithm and its different proposed cut-offs. •The EWGSOP algorithm needs further validation.•Baseline results of the SarcoPhAge study are presented in this paper.•Sarcopenic subjects had a worse quality of life for the domain of physical functioning.•Sarcopenia seems to be associated with many harmful clinical components.